Sociological studies of children and youth. Vol. 10 special international volume (Amsterdam : Elsevier, 2005)
This International Volume of Sociological Studies of Children and Youth shows the breadth of current empirical research that focuses on children and youth around the world. Coming from a range of methodological and theoretical orientations, this volume showcases the lives of children and the policies that shape children's lives on five continents. Across these research articles, it becomes clear that we cannot continue to assume a certain meaning of childhood, because this concept is bound by both cultural and structural factors. Cultural expectations influence how societies view children and how children view themselves. A handful of these studies show how immigrant children and youth provide particularly interesting insight as they navigate more than one cultural context. Structural factors also become salient, as children come from unequal backgrounds, different levels of economic development, and face varying political concerns. While these papers come from different doorsteps of the world, cultural and structural threads of continuity connect them as meaningful for children. This volume illustrates how international childhood researchers can use current concepts and theories into unlikely contexts exposing their limitations and helping to inform more versatile and robust lines of thinking for children and youth studies.
State of the art report.
Description based on print version record.
Keywords: Child development; Age groups: children; Age groups: adolescents; Social Science -- Children's Studies